Classical Thoracolumbar Interfascial Plane (cTLIP) Block for Perioperative Analgesia Major Spine Surgery: A Case Series - Wiliam Yuhono; I Gusti Ngurah Mahaalit Aribawa (Faculty of Medicine-Universitas Airlangga, 2026)
Introduction: Decompression-Stabilization-Fusion (DSF) procedures will continue to increase by 7% more than the aging population. Post spine surgery pain makes the thoracolumbar interfascial plane (TLIP) block an option for multimodal pain management. This block has an efficacy that is comparable to the Erector Spinae Plane Block (ESPB), which is even more selective and better for spinal surgery. Objective: This case series describes the clinical application and perioperative analgesic outcomes of ultrasound-guided classical thoracolumbar interfascial plane (cTLIP) block with dexamethasone in patients undergoing lumbar spine surgery. Case Series: The authors present three cases of lumbar vertebrae fracture at L1 (CV L1) Frankel E with physical status American Society of Anesthesiologists (ASA) physical status II undergoing DSF. All patients underwent general anesthesia (GA-OTT) with a cTLIP block using 20 mL of 0.25% bupivacaine and 2 mg dexamethasone on both sides at level thoracal T12. Patients were extubated and monitored intra- and postoperatively for opioid requirements, numerical pain scale (NRS) at hours 0, 1, 6, 12, 24, and 48, time to first opioid rescue, and length of stay (LOS). The results showed an analgesia duration of 8-9 hours. Opioids were used except during induction and rescue. The opioid requirement within 24 hours postoperative in all three cases appeared to decrease. There was also no Postoperative Nausea and Vomiting (PONV) event, which is associated with the use of the TLIP block. Additionally, the LOS for each patient in this case series was 4 days. Conclusion: With a duration of 8 to 10 hours, the cTLIP block using dexamethasone adjuvant offers excellent pain control during and after the procedure. This leads to a marked decrease in opioid consumption within the first 24 hours, which improves recovery.